Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite

Kinetic investigation on palladium-catalyzed carbonylation of allyl alcohol - Tonde, Sunil S.; Rajurkar, Kalpendra B.; Pagar, Nitin S. (International Journal of Chemical Kinetics, 2025)
Palladium-catalyzed carbonylation of allyl alcohol to 3-butenoic acid has been investigated. A significant effect of halide promoters, p-tolylsulfonic acid (TsOH), water, solvents, and PPh3 concentration activity and selectivity has been studied. Detailed kinetics of this reaction was investigated in a temperature range of 363-383 K. The influence of parameters such as stirring speed, allyl alcohol, catalyst, benzyltriethylammonium chloride (BTEAC), TsOH concentrations, and CO partial pressures on the activity and selectivity has been studied. An empirical rate equation was suggested and found to be fairly consistent with observed rate data. In addition, the activation energy and kinetic parameters were evaluated.
Keywords: allyl alcohol; Carbonylation; halide promoters; kinetics; Mechanism; Palladium